Principles and practice of ground improvement - Han, Jie, 1964- (Hoboken, New Jersey : Wiley, 2014)
"The proposed book focuses on the principles and design of ground improvement technologies"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Soil stabilization; Foundations; TECHNOLOGY & ENGINEERING / Civil / General